Level Of Dribbling Skills In Futsal Games Among Extracurricular Players Of Himajas Putri At Dehasen University Bengkulu - Donika Restami; Roni Syaputra; Feby Elra Perdima (Journal of Multidisciplinary Research, 2026)
This study aims to determine the level of dribbling skills in futsal games in extracurricular players of female Himajas at Dehasen University, Bengkulu with a quantitative descriptive research type with a sample of 20 players. The data collection instrument uses a standardized dribbling skills test. The results of the study show that the futsal dribbling skills of female Himajas players obtained the fastest value of 8.76 and the lowest value of 17.23 with an average of 13.03 in the moderate category. Futsal dribbling skills of female Himajas players are in the good and moderate categories with data acquisition in the "Very Good" category there are none, the "Good" category is 9 people and 6 people with a percentage of 43% and 29%, the "Moderate" category is 12 people and 8 people with a percentage of 57% and 38%, the "Poor" category is none shooting and in dribbling there are 7 people with a percentage of 33% and there are no players in the Very Poor category.